Mesozooplankton responses to oceanographic conditions across different scales in Salinas Bay, Northern Pacific coast of Costa Rica during 2011-2013 - Morales-Ramírez, Álvaro; Till Pons, Ivana; Alfaro, Eric J.; Corrales-Ugalde, Marco; Sheridan-Rodríguez, Carolina (Revista de Biología Tropical, 2021)
Introduction: The North Pacific of Costa Rica is characterized by presenting a variation of the subsurface temperature of the sea (SSST) modulated by surface winds with east component, with seasonal and intra-seasonal variations. The SSST is fundamental for the interactions of the ocean-atmosphere interface and influence marine biological processes. Zooplankton studies in the North Pacific are scarce and have been focused on the composition, abundance and biomass of macro and mesozooplankton in Culebra Bay. No works on zooplankton has been carried out northward of Papagayo Gulf. Objective: To analyze the variation of the zooplankton in Bahía Salinas at different scales in response to oceanographic-atmospheric conditions. Methods: during 2011, 2012 and 2013, mesozooplankton was collected in seven stations following a coastal-ocean gradient to determine abundance, biomass, and community composition. CTD casts were also carried out in each station. Hourly data of the Sea Subsurface Temperature (SSST) were obtained from June 2003 to December 2017. Results: The annual surface temperature in Bahía Salinas was lower in December-April with a secondary minimum in July and higher in May-June and August-November. The cold, neutral and warm events determined by anomalies in the SSST, presented a distribution of the temperature in the water column with horizontal stratification, vertical mixture and homogeneous, respectively. The spatial distribution of zooplankton did not show significant differences and the variation of the total average abundance and biomass showed a similar behavior during the study period, with less variation in the first year compared to the second one, being the copepods the predominant category for all the dates. On a seasonal scale, a general pattern of variation between dry and rainy seasons was not observed, and copepods and others zooplankton groups were the categories that presented differences. On an intra-seasonal scale, abundance and biomass showed an inverse relationship with SST. Copepods and gelatinous zooplankton (GZ) were differentiated in all events. Conclusions: The zooplankton of Bahía Salinas respond differentially at different scales to the climatic conditions that affect the SSST of the region. The classification of the sampling dates into events allows characterizing different profiles in the water column it also allows to define the variation patterns for mesozooplankton that reflects short-term adaptation as a function of variation in environmental conditions. These findings help to understand how oceanographic processes determine plankton community composition and biota in general. This is relevant in times of climate change and the manifestation of its impact through processes such as ocean acidification and loss of marine biodiversity.